Comparative Study on the Implementation of Knowledge Management Systems for Aglaonema Farmers: A Structured Method and UML Object Approach - Sugiarti, Yuni; Suroso, Arif Imam; Hermadi, Irman; Sunarti, Euis (International Journal of Engineering, Science and Information Technology, 2025)
Aglaonema farming holds significant economic potential, but challenges in knowledge management often hinder farmers' productivity. Knowledge Management Systems (KMS) provide effective solutions for managing knowledge efficiently. This study aims to conduct a comparative analysis of KMS implementation for aglaonema farmers using a structured method and an object-oriented method with the Unified Modeling Language (UML). The research methodology includes identifying farmers' needs, developing systems using both approaches, conducting functionality testing, and performing a comparative analysis based on effectiveness, efficiency, and ease of use. The study's results indicate that the object-oriented approach with UML offers greater flexibility in development and adaptation to changing user needs. At the same time, the structured method provides stability within a well-defined system. User evaluations reveal a preference for UML-based systems, particularly in supporting dynamic knowledge access and integrating market price prediction features. The study concludes that the object-oriented approach with UML is more suitable for KMS development in agribusiness, where an adaptive and responsive system is essential.